2004
DOI: 10.1007/s10162-003-3003-8
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Monaural Spectral Cues Is Enhanced in the Presence of Cues to Sound-Source Lateral Angle

Abstract: The contention that normally binaural listeners can localize sound under monaural conditions has been challenged by Wightman and Kistler (J. Acoust. Soc. Am. 101:1050Am. 101: -1063Am. 101: , 1997, who found that listeners are almost completely unable to localize virtual sources of sound when sound is presented to only one ear. Wightman and Kistler's results raise the question of whether monaural spectral cues are used by listeners to localize sound under binaural conditions. We have examined the possibility th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The results presented here suggest that these benefits do indeed carry over into localization when listeners move, as listeners often do in everyday life. Martin et al (2004) and also Wightman and Kistler (1997) have shown that, in order for high-frequency spectral cues to be useful for front-back discrimination, binaural cues for the lateral displacement of the sound source are probably necessary. Also, Janko et al (1997) implemented a neural net model and found that monaural spectral cues only contained enough information to produce localization results on a par with human listeners if the ITD that would specify lateral sound source location was also provided.…”
Section: A Comparison To Previous Related Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results presented here suggest that these benefits do indeed carry over into localization when listeners move, as listeners often do in everyday life. Martin et al (2004) and also Wightman and Kistler (1997) have shown that, in order for high-frequency spectral cues to be useful for front-back discrimination, binaural cues for the lateral displacement of the sound source are probably necessary. Also, Janko et al (1997) implemented a neural net model and found that monaural spectral cues only contained enough information to produce localization results on a par with human listeners if the ITD that would specify lateral sound source location was also provided.…”
Section: A Comparison To Previous Related Resultsmentioning
confidence: 99%
“…Notwithstanding the work of Martin et al (2004), Wightman and Kistler (1997), and others, the degree to which spectral shape cues can be used monaurally, without binaural difference cues to provide an estimate of laterality, is still the subject of considerable debate and research (e.g., Hofman and van Opstal, 2003;Jin et al, 2004;Searle et al, 1975).…”
Section: Monaural Spectral and Level Cuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall mean elevation error was around 14 for the 2° azimuth window which confirms that spectral cues to elevation were reduced. [The mean elevation error is normally around 8° for a brief white noise stimulus (Martin et al, 2004 )]. A One-Way repeated-measures ANOVA revealed a significant effect of azimuth window, F (3.0, 21.1) = 10.8, p < 0.001, partial η 2 = 0.61.…”
Section: Resultsmentioning
confidence: 99%
“…For signals with high-frequency information of sufficient bandwidth, NH listeners can often reliably distinguish front from back sound source location by exploiting differences in the pattern of high-frequency spectral shape cues that may be extracted from the head-related transfer function (created by the interference of the head, pinnae, and torso, see Hebrank & Wright 1974; Zahorik et al 2006). However, Janko et al (1997, with a neural net model), Wightman & Kistler (1997, for human behavioral data), and Martin et al (2004), found that high-frequency spectral shape cues were only useful for front-back discrimination when the correct interaural difference cues were also available (see Pastore et al 2020a for an in-depth discussion).…”
Section: Introductionmentioning
confidence: 99%